Answer:
[tex]f\left(x\right)=\cos\left(x\right)\: and\:\: g\left(x\right)=\left(2x^2-1\right)[/tex]
Step-by-step explanation:
We have, [tex]H\left(x\right)=\cos\left(2x^2-1\right)H ( x )[/tex]
[tex]=\cos\left(2x^2-1\right)[/tex]
And [tex]H\left(x\right)=\left(f\:\circ\:g\right)\left(x\right)H ( x ) = \left(f\:\circ\:g\right)( x )[/tex]
[tex]\Rightarrow \left(f\:\circ\:g\right)(x)=\cos\left(2x^2-1\right)[/tex]
Now, [tex]f\left(x\right)=\cos\left(x\right)[/tex] and [tex]g\left(x\right)=\left(2x^2-1\right)[/tex]